2006
DOI: 10.1063/1.2167610
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dissolved nitrogen in improving barrier properties of ruthenium

Abstract: Diffusion barrier properties of 10nm Ru sputtered in N and Ar atmospheres have been assessed. N was found to be dissolved in the Ru film deposited in N atmosphere making it amorphous with ten times higher sheet resistance. Annealing caused effusion of N resulting in crystallization of Ru and a sharp decrease in sheet resistance. The incorporation of N delayed the Ru silicide formation and reduced Cu and Ru diffusion into the SiO2 dielectric layer. These beneficial performances are attributed to dissolved N in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(59 citation statements)
references
References 6 publications
(3 reference statements)
1
58
0
Order By: Relevance
“…This may be attributed to that the addition of "N" makes the Ta grain thin, and makes the Ta-N tends to be nano-crystalline or amorphous-like (Damayantia et al, 2006). So the surface of Ta-N is smoother than the others.…”
Section: Fig 2 -Afm Images Of As Deposited and 400 • C/300 S Fa Sampmentioning
confidence: 87%
“…This may be attributed to that the addition of "N" makes the Ta grain thin, and makes the Ta-N tends to be nano-crystalline or amorphous-like (Damayantia et al, 2006). So the surface of Ta-N is smoother than the others.…”
Section: Fig 2 -Afm Images Of As Deposited and 400 • C/300 S Fa Sampmentioning
confidence: 87%
“…Unfortunately, RuN is known to be very unstable. Most of the N in RuN is released upon annealing at 275 C, inducing some unfavorable phenomenon [14,15,32]. Wu et al and Ihara et al reported that there were a large amount of nitrogen vacancies formed by N effusion in RuN after annealing [15,33].…”
Section: Resultsmentioning
confidence: 97%
“…Damayanti et al reported that these advantages can be attributed to the N atoms dissolved and stuffed in the grain boundaries (GBs) of Ru films. Unfortunately, RuN is known to be decomposed after annealing at 275 C [14,15]. Consequently, enhancing thermal stability of RuN becomes critical for improving the barrier performance of Ru film.…”
Section: Introductionmentioning
confidence: 99%
“…5 To prevent formation of Ru x Si y , multilayers of ruthenium nitrides have been used to impart superior barrier properties. [6][7][8][9] In these previous studies, 10-nm-thick amorphous RuN thin film was shown to block Cu diffusion after annealing at 350°C for 30 min. 6 RuN, RuTa, and Ru-TaN thin films with thickness of 15 nm have failure temperatures of 600°C, 700°C, and 900°C, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9] In these previous studies, 10-nm-thick amorphous RuN thin film was shown to block Cu diffusion after annealing at 350°C for 30 min. 6 RuN, RuTa, and Ru-TaN thin films with thickness of 15 nm have failure temperatures of 600°C, 700°C, and 900°C, respectively. 7,8 Such barrier films are attractive due to their compatibility with direct Cu electroplating.…”
Section: Introductionmentioning
confidence: 99%